ENVIRONMENTAL PARASITOLOGY: SOIL ANALYSIS FOR GEOHELMINTH LARVAE CONTAMINATION IN ILHÉUS, BAHIA - Souza Silva, Yasmine; Mendes Silva da Silva, Júllyan; Cardoso Castro, Ricardo; de Oliveira Dias, Sandro; Santos Carvalho, Sílvia Maria; Fernandes da Silva, Marcelo (Revista de Patologia Tropical / Journal of Tropical Pathology, 2017)
The study of parasitic soil contamination is important for monitoring biohazards in densely populated areas or those with high anthropic activities. The present study quantified geohelminth larvae in two estuaries in the urban area of Ilhéus, Bahia; one to the north, formed by the Almada River and another to the south, in the Pontal Bay. The collections were performed following standard methodology considering climactic conditions and local tide tables; the Rugai method with modifications was used to analyze soil sediments. Morphological results showed a significantly higher number of Strongyloides stercoralis larvae in the estuary of the Almada River from September to December, coinciding with higher temperatures and lower rainfall and humidity. However, there was significant variation in climatic conditions and in the classification of anthropic activity interfering in the frequency and diversity of soiltransmitted helminth larvae, which justifies its monitoring to ensure environmental health in areas frequented by residents and tourists in Ilhéus, Bahia